Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2005
DOI: 10.1145/1054972.1055013
|View full text |Cite
|
Sign up to set email alerts
|

Comparing cursor orientations for mouse, pointer, and pen interaction

Abstract: Most graphical user interfaces provide visual cursors to facilitate interaction with input devices such as mice, pointers, and pens. These cursors often include directional cues that could influence the stimulus-response compatibility of user input. We conducted a controlled evaluation of four cursor orientations and an orientationneutral cursor in a circular menu selection task. Mouse interaction on a desktop, pointer (i.e. wand) interaction on a large screen, and pen interaction on a Tablet PC were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 37 publications
(39 reference statements)
2
29
0
Order By: Relevance
“…They found that feedback of any type decreases the final positioning time (between entering the target an selecting it) but has no significant effect on overall completion time. Regarding cursor shape, Po et al [17] compared a circle cursor and four arrow cursors (upper-left, upperright, lower-left and lower-right) and showed that (i) an arrow cursor is more efficient when it is oriented in the direction of movement and that (ii) a circle cursor is the most efficient on average and its performance is independent of the movement angle.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that feedback of any type decreases the final positioning time (between entering the target an selecting it) but has no significant effect on overall completion time. Regarding cursor shape, Po et al [17] compared a circle cursor and four arrow cursors (upper-left, upperright, lower-left and lower-right) and showed that (i) an arrow cursor is more efficient when it is oriented in the direction of movement and that (ii) a circle cursor is the most efficient on average and its performance is independent of the movement angle.…”
Section: Related Workmentioning
confidence: 99%
“…It remains visible whichever edge it is pushed against ( Figure 3). This factor will help assess whether the observed effects of Angle and Edge are due to the arrow cursor orientation [17]. …”
Section: Study 1: Relevant Factorsmentioning
confidence: 99%
“…For example, the cursor might turn into a pointing hand if it is over an hyper-link or into a typewriter cursor if it is inside an editable text area. However, although there are several studies on 2D cursor shapes [20,21], they are only focused on 2D content.…”
Section: Visual Cursorsmentioning
confidence: 99%
“…Po, Fisher, and Booth (2005) remark that modern GUIs are still using more or less the same original cursors that came about in the mid 1970's. These cursors were partially crafted based on the hardware constraints of the time.…”
Section: Inadequacy Of Single-user Guis For Passive Viewersmentioning
confidence: 99%